1998
DOI: 10.1002/hep.510270134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rate of sequence variation in the hypervariable region of E2/NS1 region of hepatitis C virus in normal and hypogammaglobulinemic patients

Abstract: The hypervariable region (HVR) of the E2/NS1 region of hepatitis C virus (HCV) varies greatly between viral isolates with high rates of genomic change reported during the course of chronic infection. The HVR is thought to encode a structurally unconstrained envelope protein containing several linear B cell epitopes recognized by neutralizing antibody. It has been postulated that amino acid changes in the HVR could result from humoral immune pressure leading to the selection of escape mutants. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
96
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 24 publications
10
96
1
1
Order By: Relevance
“…22 Several studies suggest that humoral immune pressure leads to selection of specific species that may be more capable of evading the host immune response. 23,24 Full sequence evaluation of clones would be necessary to evaluate specific humoral and cellular responses to epitopes derived from clonal variants. This has not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several studies suggest that humoral immune pressure leads to selection of specific species that may be more capable of evading the host immune response. 23,24 Full sequence evaluation of clones would be necessary to evaluate specific humoral and cellular responses to epitopes derived from clonal variants. This has not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,30,31 We conducted a longitudinal study of virus mutation in individual patients, rather than a cross-sectional study, as this is a more appropriate methodology for observing the natural history of virus-host interactions. Many earlier studies have included patients carrying a variety of HLA types, infected with differing HCV genotypes for varying periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported lower rates of coding mutation in antibody deficient compared with immunocompetent patients. 13,14 This has been interpreted as evidence that mutation in the HVR is selected by the host antibody response. However, a review of the data reveals a lower frequency of both cryptic and coding mutations in the antibody deficient patients when compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Also, antibodies may play a role here because an early antibody recognition of the hypervariable region 1 (HVR1) in the envelope E2 protein was correlated with virus clearance (Allander et al, 1997), and infection of chimpanzees could be inhibited by a human hyperimmune serum against HVR1 (Farci et al, 1996). In line with this are studies on the rate of HVR1 evolution that have suggested that the HVR1 region is under immune pressure exerted by neutralizing antibodies (Booth et al, 1998;Kato et al, 1993; Shimizu et al, 1994;Weiner et al, 1992). Nevertheless, by using infectious retroviral pseudotypes, a recent study has shown that neutralizing antibody responses early after infection do not seem to play a role in the resolution of an acute infection (Logvinoff et al, 2004 aspect is that HCV seems to have a wide cell tropism and can infect not only hepatocytes but also cells of the immune system (Bain et al, 2001;Sung et al, 2003).…”
mentioning
confidence: 97%